Comparable outcomes of haploidentical, 10/10 and 9/10 unrelated donor transplantation in adverse karyotype AML in first complete remission. Issue 10 (3rd September 2018) - Lorentino, Francesca; Labopin, Myriam; Bernardi, Massimo; Ciceri, Fabio; Socié, Gerard; Cornelissen, Jan J.; Esteve, Jordi; Ruggeri, Annalisa; Volin, Liisa; Yacoub‐Agha, Ibrahim; Craddock, Charles; Passweg, Jacob; et al.
Abstract: Allogeneic hematopoietic stem cell transplantation (HSCT) is the most powerful therapy preventing relapse in patients with adverse cytogenetics acute myeloid leukemia (AML) in first complete remission (CR1). In the absence of a matched related donor, potential alternatives include 10/10, 9/10 HLA‐matched unrelated (UD) or haploidentical (Haplo) donors. We analyzed clinical outcomes of patients undergoing T‐cell repleted Haplo ( n = 74), 10/10 UD ( n = 433) and 9/10 UD HSCT ( n = 123) from 2007 to 2015, reported to the EBMT Registry. Adverse risk AML was defined according to the 2017 ELN cytogenetic risk classification. The 2‐year nonrelapse mortality was 19% for Haplo, 18% for 10/10 UD and 18% for 9/10 UD ( P = .9). The relapse incidence was not significantly affected by donor source, with a 2‐year incidence of 27% for Haplo HSCT, 39% for 10/10 UD and 37% for 9/10 UD SCT ( P = .3). We show comparable probabilities of leukemia‐free survival (LFS) and overall survival (OS) at 2 years among Haplo HSCT, 10/10 UD SCT and 9/10 UD SCT (53% and 59%, 43% and 50%, 44% and 50%, respectively, P = .5 for both parameters). The type of donor was not significantly associated with either acute or chronic graft‐vs.‐host disease incidence. Using multivariable Cox model, Haplo HSCT recipients experienced comparable OS and LFS to 10/10 and 9/10 UD. In the present series of adverse cytogenetics AML patients in CR1, Haplo HSCT recipients had comparable outcomes to those of 10/10 and 9/10 UDs, suggesting that all these types of HSCT may be considered a valid option in this high risk population.